The impact of islands image on tourists’ satisfaction and place identity - Loureiro, S. M. C.; Kaufmann, H. R. (Journal for International Business and Entrepreneurship Development, 2013)
The main goal of this study is to provide a contribution to the newly emerging field of place identity by studying the relationship between the dimensions of place image and satisfaction, as well as between the dimensions of place image and place identity. Based on previous literature, a model was tested using tourists who stayed in Sao Tome and Principe islands. The main findings suggest that typicality (houses, handcraft, and facilities), place quality (beaches, resorts, and accommodations), and agreeableness (friendship of local habitants, quiet place, climate, nature, coffee and cocoa plantations) have a significant effect on satisfaction and place identity.